Does 5, 7-Dihydroxytryptamine injection into nucleus accumbens cause hyperacusis?. (13th July 2019) - Mokrian, Helnaz; Nasirinezhad, Farinaz; Shahbazi, Ali; Danyali, Samira; Jalaei, Shohreh; Karimi, Minoo; Farahani, Saeid
Highlights: Depletion of serotonergic neurons in nucleus accumbens cause large amount of hyperresponsivity to sounds. Injury to nucleus accumbens without depletion of serotonergic neurons cause small amount of hyperresponsivity to sounds. The presence of background noise can eliminate hyperresponsivity to sounds. Hyperresponsivity to sounds happens in different high intensities. Abstract: Hyperacusis may be defined as diminishing tolerance to moderate and high intensity sounds in people with normal hearing sensitivity. Serotonin plays a critical role in some of auditory tasks including startle reflex and prepulse inhibition. Serotonin deficiency can cause some diseases which can coincide with hyperacusis. The aim of the present study was to investigate the probable influence of serotonergic depletion in nucleus accumbens (NAcc) on the startle reflex. The startle reflexes were examined in Wistar rats (n: 48) in different intensities with and without the background noise. The amplitude of startle reflex significantly increased in NAcc-injected rats without background noise, while this difference disappeared in the presence of background noise in all intensities. These data proposed that the injection of 5, 7-Dihydroxytryptamine (5, 7-DHT) into nucleus accumbens will cause hyperacusis-like behavior, and strengthens the possibility of the role of serotonin and nucleus accumbens in hyperacusis.